Upregulated integrin α11 in the stroma of cutaneous squamous cell carcinoma promotes skin carcinogenesis - Martínez-Nieto, Guillermo A.; Teppo, Hanna-Riikka; Petrelius, Noora; Izzi, Valerio; Devarajan, Raman; Petäistö, Tiina; Liu, Hengshuo; Kim, Kris S.; Karppinen, Sanna-Maria; Ruotsalainen, Heli; Koivunen, Jarkko; Mäki, Joni M.; et al. (Frontiers in Oncology, 2022)
Integrin α111 is a collagen-binding integrin that is needed to induce and maintain the myofibroblast phenotype in fibrotic tissues and during wound healing. The expression of the α11 is upregulated in cancer-associated fibroblasts (CAFs) in various human neoplasms. We investigated α11 expression in human cutaneous squamous cell carcinoma (cSCC) and in benign and premalignant human skin lesions and monitored its effects on cSCC development by subjecting α11-knockout (Itga11-/-) mice to the DMBA/TPA skin carcinogenesis protocol. α11-deficient mice showed significantly decreased tumor cell proliferation, leading to delayed tumor development and reduced tumor burden. Integrin α11 expression was significantly upregulated in the desmoplastic tumor stroma of human and mouse cSCCs, and the highest α11 expression was detected in high-grade tumors. Our results point to a reduced ability of α11-deficient stromal cells to differentiate into matrix-producing and tumor-promoting CAFs and suggest that this is one causative mechanism underlying the observed decreased tumor growth. An unexpected finding in our study was that, despite reduced CAF activation, the α11-deficient skin tumors were characterized by the presence of thick and regularly aligned collagen bundles. This finding was attributed to a higher expression of TGFb1and collagen crosslinking lysyl oxidases in the Itga11-/- tumor stroma. In summary, our data suggest that α11b1 operates in a complex interactive tumor environment to regulate ECM synthesis and collagen organization and thus foster cSCC growth. Further studies with advanced experimental models are still needed to define the exact roles and molecular mechanisms of stromal α11b1 in skin tumorigenesis.